Avaliação da qualidade de vida de portadores de HIV/AIDS - Maia, Cynthia Marques Ferraz da (2006)
The AIDS syndrome congregates its very own characteristics and some of them interfere directly with the quality of life of people living with HIV/AIDS. The objectives of this research were to identify, to describe and to analyze the quality of life of persons living with HIV/AIDS, assisted by a support organization at the Brazilian center-west. It is an exploratory qualitative and quantitative cross-sectional study, which was carried through from February until June of 2005, at the Casa de Apoio ao Doente de AIDS (CADA). Participants answered the quality of life questionnaire from the World Health Organization (Whoqol-100), a semi-structured interview and a social-demographic and clinical information sheet, to analyze the dimensions of the quality of life of people living with HIV/AIDS (physical, psychological, level of independence, social, ambient relations) and to compare with social-demographic and clinical aspects (sex, age, schooling, civil state, religion, family income, number of dependents, existence of another person living with HIV/AIDS in the family, place of origin, clinical state, clinical treatment and current multi-professional accompaniment). The sample consisted of 18 persons, with predominance of males (61,1%); age 35 to 45 year old (44,6%), family income of one to three minimum wages (50,0%), and schooling until the second year of junior high (55,6%). Based on the analysis of the interviews, the method of coping most used was escape or avoidance (5,0%), followed by the behavioral one (2,5%), omission/control of information to a third part (2,5%), problem resolution (1,2%), focus on the positive side (1,2%) and unrealistic optimism (1,2%), and search for the control of the emotions (0,6%). It should be emphasized that the discrimination was evident in 5,5% of the participants´ stories, this fact might reflect the loss of the professional status. Regarding the psychological aspects, it was perceived the presence of stories indicating depression; fantasies related to losses and restricted social behavior. These losses had been minimized by the support received from CADA, whose role is to fortify the social support of the participants. The data from the Whoqol-100 showed that there was a 20% minimum loss of important domains in the quality of life (physical, psychological, personal level of independence and relationships), however the domain of the spirituality suffered the lesser impact. From the data collected, it is suggested that the support houses should develop therapeutical and production workshops, to develop self-esteem, the capacity for professional work, the level of autonomy and the quality of life of the persons living with HIV/AIDS.